Binder-free nanostructured germanium anode for high resilience lithium-ion battery. (10th April 2022) - Fugattini, S.; Gulzar, U.; Andreoli, A.; Carbone, L.; Boschetti, M.; Bernardoni, P.; Gjestila, M.; Mangherini, G.; Camattari, R.; Li, T.; Monaco, S.; Ricci, M.; et al.
Highlights: Binder-free nanostructured germanium anode for lithium-ion batteries. Capacity retention of 95% after 1600 cycles at 1C. Specific capacity of 1060 mAh g −1 at 10C and 450 mAh g −1 at 60C. Tested from -30 °C to +60 °C. Realized by means of a two-step process, easily scalable for industrial applications. Abstract: The development and the characterization of a nanostructured binder-free anode for lithium-ion batteries exploiting the germanium high theoretical specific capacity (1624 mAh g −1 for Li22 Ge5 alloy) is herein presented. This anode secures remarkable performances in different working conditions attaining a 95% capacity retention at 1C (i.e., 1624 mA g −1 ) after 1600 cycles at room temperature and a specific capacity of 1060 mAh g −1 at 10C and 450 mAh g −1 at 60C. The nanostructured binder-free germanium-based anode shows also strong resilience in terms of temperature tests, being it tested from -30 °C to +60 °C. Indeed, the specific capacity remains unaltered from room temperature up to +60 °C, while at 0 °C the cell is still retaining 85% of its room temperature capacity. In a full-cell configuration with LiFePO4 as cathode, the Ge anode showed a stable specific capacity above 1300 mAh g −1 for 35 cycles at C/10. Concerning the fabrication procedure, a two-step realization process is applied, where a Plasma Enhanced Chemical vapor Deposition (PECVD) is employed to grow a germanium film on a molybdenum substrate followed by hydrofluoric acid (HF) electrochemical etching, the latter having the scope of nanostructuring the Ge film. Finally, compositional, morphological, and electrochemical characterizations are reported to fully investigate the properties of the binder-free nanostructured germanium anode here disclosed. Abstract : Image, graphical abstract .